Algorithms with stabilizing coefficients for solving poorly determined radiophysics problems - Kurayev, A.A.; Matveyenko, V.V.; Popkova, T.L. (Радіофізика та електроніка, 2016)
This article describes the algorithms with correcting and stabilizing coefficients to provide sustainable solutions to systems of equations related to poorly determined tasks of electrodynamics and nonlinear dynamics. It demonstrates the use of the modified algorithms in the task of E0i-waves propagation in irregular waveguide and dynamic model of Rössler’s chaos. In the latter case the article demonstrates that “deterministic” (i. e. regenerating) chaos is impossible.